2021
DOI: 10.1515/jpem-2020-0533
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution in trunk and legs are associated with cardiometabolic risk clustering among Chinese adolescents aged 10–18 years old

Abstract: Objectives The aim of the present study was to evaluate the association of body fat distribution with cardiometabolic risk factors clustering among Chinese adolescents. Methods In this cross sectional study a total of 1,175 adolescents aged 10–18 years underwent a comprehensive assessment of cardimetabolic risk factors. Body fat analysis was performed with bioelectrical impedance analysis (BIA). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although several studies have shown that fat distribution might be as relevant as total fat mass in stratifying the cardiovascular risk (11,55), to our knowledge, no studies have found differences in FFMI of upper and lower limbs in relation to vascular properties. Accordingly, while increased levels of lower limb fat mass would work as a protective factor of cardiovascular disease in children, adolescents, and adults (53), increased arm fat mass was strongly associated with CRFs in women (59). Further studies, considering segmental body composition characteristics and cardiovascular properties are needed to further clarify these observations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although several studies have shown that fat distribution might be as relevant as total fat mass in stratifying the cardiovascular risk (11,55), to our knowledge, no studies have found differences in FFMI of upper and lower limbs in relation to vascular properties. Accordingly, while increased levels of lower limb fat mass would work as a protective factor of cardiovascular disease in children, adolescents, and adults (53), increased arm fat mass was strongly associated with CRFs in women (59). Further studies, considering segmental body composition characteristics and cardiovascular properties are needed to further clarify these observations.…”
Section: Discussionmentioning
confidence: 97%
“…Our data suggest that variations in total body fat mass or central fat mass (trunk) are associated (albeit weakly) with changes in arterial properties. Evidence has suggested that trunk fat mass as well as abdominal obesity should be considered as real CRFs (35,37,52,53). Indeed, trunk fat mass and abdominal fat have shown a strong correlation between each other in adult women (54).…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) is an indicator that is commonly used to diagnose obesity, but measuring body composition is a better tool for diagnosing obesity because it gives information on body fat mass while BMI makes no distinction between adipose tissue and lean mass 7 . Fat distribution in the body is also an important factor in determining the risk of chronic metabolic diseases 8 . Waist circumference, waist to hip, and waist to height ratios are indicators of abdominal obesity that can be used along with BMI to give more information about obesity 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The risk largely depends on the distribution of adipose tissue ( Santilli et al, 2017 ). Trunk fat and waist circumference (WC) are associated with type 2 diabetes, cardiovascular disease, and multiple metabolic risk factors ( Xu et al, 2015 ; Yang et al, 2019 ; Yang et al, 2021 ). However, these findings may have been confounded by unmeasured confounding risk factors, including objectively measured physical activity, cardiorespiratory fitness, or other underlying medical conditions that were not captured appropriately.…”
Section: Introductionmentioning
confidence: 99%